Cooling rates and peak temperatures during friction stir welding of a high-carbon steel. (1st January 2015) - Manvatkar, V.; De, A.; Svensson, L.-E.; DebRoy, T.
Abstract : Friction stir welding can potentially avoid the need for post weld heat treatment for the welding of high-carbon steels. Although control of both peak temperature and cooling rate has been suggested to achieve this goal, the current literature does not provide any help with selecting appropriate welding variables. In order to address this problem, here we present a set of easy-to-use maps of both the cooling rates and the peak temperatures for various welding conditions during friction stir welding of a high-carbon steel.